Respuesta :
Answer: A. (4,1)
Step-by-step explanation:
2x -5y = 3
x -3y = 1
Change the equation to isolate a variable so you can substitute it in the other one.
x = 1+3y so
2(1+3y) -5y = 3
2 + 6y -5y =3
2 + y = 3
y=1
Back to the easy equation we isolated
x = 1+3(1)
x= 4
(4,1) is a point where x=4 and y=1
Solve using elimination method-
Eliminate the x’s
Distribute -2
-2x + 6y = -2
Subtract
2x - 5y = 3
-2x + 6y = -2
y = 1
Plug it in:
x - 3 = 1
x = 4
Solution
(4,1)
confirm:
2(4) - 5(1) = 3
Eliminate the x’s
Distribute -2
-2x + 6y = -2
Subtract
2x - 5y = 3
-2x + 6y = -2
y = 1
Plug it in:
x - 3 = 1
x = 4
Solution
(4,1)
confirm:
2(4) - 5(1) = 3